Influence of mica mineral on flame retardancy and mechanical properties of intumescent flame retardant polypropylene composites - Kahraman Merve; Kızılcan Nilgün; Oral Mehmet Ali (Open Chemistry, 2021)
In many plastic applications, improvement of the flame retardancy is a very significant topic. Polypropylene (PP) is used in many applications such as housing industry due to its cost performance efficiency. Enhancement of flame retardancy properties of PP is necessary in many applications. In this study, the investigation focuses on the synergistic effect of mica mineral and IFR in enhancing the flame retardancy properties of PP in order to achieve cost competitive solution, so as to provide that different/various ratios of IFR and mica mineral were added into PP to compose 30 wt% of the total mass of the polymeric compounds. The synergistic effect of mica mineral with IFR in PP was investigated by limiting oxygen index (LOI), glow wire test (GWT), UL-94 test, thermal gravimetric analyses (TGA), and mechanical tests. The results from LOI, UL 94, and GWT tests indicated that mica added to PP/IFR compound has a synergistic flame retardancy effects with the IFR system. When the content of mica was 6 wt%, LOI value of PP compound reaches to 34.9% and becomes V-0 rating (3.2 mm) in UL 94 flammability tests and compounds pass GWT tests both at 750 and 850°C.